SISTEM INFORMASI PENJUALAN BARANG PADA SEMESTA ART GALLERY - Waluyo, Tri; Retnoningsih, Dwi; Anwariningsih, Sri Huning (2086-4221, 2012)
Technology in the business world increasingly plays an important role. One of them is  the application of a computerized of sales  information system on the company for  the work  efficiency. This ways is more and more often used because it useful for storage of data and make  the search for data or information easier, in order avoid the usual dereliction that usually find in the manual storage systems. Various problems that often arise as a result of manually managing on Semesta Art Galery are: (a) the stock of goods in warehouse is difficult to be controlled, (b) high risk loss data of purchase and sales transaction, and (c) recording system of non-cash sales / credit is not optimal. The objectivity of the research is to build sales information system on Semesta Art Galery in case for: 1) change the manual sales system into computerized systems. 2) Increasing  sales by adding non-cash  sales menu  /  credits on  software that  is built  so hoped  non-cash  sales system  can  increase the number  of costumers, and 3)helps the staff  in processing of goods  sale data,  supplier data  reports,  reports  sales, and bill of sales transaction.  This  system  is build  using the  waterfall method (the life  cycle of software) and uses the programming language Visual Basic 6.0, SQL Server 7. based on  results of  testing  system using Mc Call method, show a total value of the quality is 75.4% with the conclusion that: 1) the sales information system is easy to learn and operate by the user, 2) can run on hardware and operating systems that exist in the Semesta Art Gallery, 3) has good level in efficiency, very effective to minimize the errors  that occur, and  is hoped can be used as a  tool to optimize  sales  system  in  the Semesta Art Gallery.